MODERASI BERAGAMA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: SYSTEMATIC LITERATURE REVIEW - A’zizah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to systematically examine learning strategies of Islamic Religious Education based on religious moderation using a Systematic Literature Review (SLR) approach. The SLR method was employed to identify, evaluate, and synthesize relevant findings from national and international scholarly articles. The results indicate that religious moderation-based IRE learning strategies are implemented through the integration of moderation values into curricula and learning materials, the application of dialogical and participatory learning methods, strengthening teachers’ roles as role models, and creating supportive educational environments. Learning oriented toward religious moderation values contributes significantly to shaping students’ tolerant character and their ability to live harmoniously in diversity. Nevertheless, several challenges remain, including limited teacher understanding, insufficient policy support, and variations in socio-cultural contexts across educational institutions. Therefore, strengthening teacher competence, developing integrative curricula, and providing sustainable policy support are essential to ensure the effective implementation of religious moderation-based Islamic Religious Education.